Tepung Premix Cookies Berbahan Dasar Mocaf dan Sagu Dengan Perlakuan Penyangraian Suhu Yang Berbeda: Flour Premix Cookies Made from Mocaf and Sago with Different Roasting Temperatures - Kurniawati, Elly; Agustina, Anis (JOFE : Journal of Food Engineering, 2024)
Flour premix cookies are used as an alternative to making processed food in an instant way. Flour premix cookies are made by mixing mocaf, sago, powdered sugar, milk powder, and baking powder. This study aims to determine the relationship between mocaf and sago formulations and different roasting temperatures on the value of water content (premix flour), texture (cookies), and organoleptic (cookies) based on the best formulation. Formulation of mocaf and sago as the main factor F1 (75:25), F2 (50:50), and F3 (25:75) and roasting temperature as the second factor P1 (no roasting), P2 (700C), and P3 (800C). This resulted in 9 treatments P1F1, P1F2, P1F3, P2F1, P2F2, P2F3, P3F1, P3F2, and P3F3. The results of this study are that the higher the roasting temperature, the lower the water content, texture, and the decrease in the level of preference.